Interactive Flat Panels for Early Childhood Cognitive and Social Development: A Pedagogical Framework - Warniati Meiyani; Agus Sriyanto; Elyaum Farihah; Fauziah Hasan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the use of Interactive Flat Panels (IFP) in supporting early childhood development at Tunas Rimba II Walikukun Kindergarten. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation involving 3 teachers and 25 students aged 4–6 years. Data analysis was carried out through data reduction, data presentation, and drawing conclusions referring to the Miles and Huberman model. The results showed that the use of IFP increased children's engagement and motivation to learn through interactive visual media, with most students demonstrating noticeably higher active participation and sustained attention during IFP-based sessions compared to conventional teaching methods, while also contributing to cognitive development, fine motor skills, and social interaction. The main obstacle found was the limited competence of teachers in operating the technology. Therefore, adaptive learning strategies and strengthening of teachers' digital literacy are needed so that the use of IFP can run optimally